Citation practice in the whole TESOL master’s theses by Vietnamese postgraduates - Nguyen, Thi Thuy Loan; Issra Pramoolsook, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Citing previous works is an important rhetorical feature of academic writing and it is challenging for novice writers, especially non-native English writers (NNEWs). However, little is known about how NNEWs cite in each chapter of their master’s (M.A.) theses. This paper thus reports on the citation practice in 24 TESOL M.A. theses written by Vietnamese students. Citation types were first searched on the Antconc software with the use of the Regular Expressions (Regex) written for both conventional and ‘invented’ citing ways by this group of writers, and then based on Thompson and Tribble’s (2001) framework, citation functions were investigated and classified. Semi-structured interviews were also conducted with thesis writers and thesis supervisors. Besides the general citation practice by this group of NNEWs, and the different citation functions and types in different chapters of their theses, the study also found that these writers were not fully aware of the significance of citations as a rhetorical device in their thesis writing, and insufficient attention was paid to the in-text citations in the TESOL discourse community in Vietnam. These findings suggest explicit instructions on citations in order to help novice writers to fully acquire the citation use.